Increases in orbitofrontal cortex thickness following antidepressant treatment are associated with changes in resting state autonomic function in adolescents with major depression – Preliminary findings from a pilot study. (30th November 2018) - Koenig, Julian; Westlund Schreiner, Melinda; Klimes-Dougan, Bonnie; Ubani, Benjamin; Mueller, Bryon A.; Lim, Kelvin O.; Kaess, Michael; Cullen, Kathryn R.
Highlights: Treatment of MDD is associated with increases in HRV and cortical thickness in adults. Preliminary data in n = 12 adolescents with MDD following 8 weeks of SSRI treatment. Decreased symptoms, increased HRV and thickness of the left medial OFC at follow-up. Improvement of MDD severity was associated with increased HRV and decreased HR. Increased HRV, left lateral OFC and superior frontal cortex thickness correlated. Abstract: In adults with major depressive disorder (MDD), effective treatment has been associated with increases in both heart rate variability (HRV) and cortical thickness. However, the impact of treatment on these indices has not yet been examined in adolescents. Cortical thickness and HRV were measured in twelve adolescents with MDD before and after 8 weeks of treatment with a selective serotonin reuptake inhibitor (SSRI). We examined treatment-related changes in depression symptoms, HRV, heart rate (HR), and cortical thickness, and analyzed correlations among these change indices. At follow-up, patients showed significantly decreased depression severity, increased HRV and increased thickness of the left medial orbitofrontal cortex (OFC). Clinical improvement was associated with increased HRV and decreased HR. Increased HRV was associated with increased cortical thickness of left lateral OFC and superior frontal cortex. Due to the small sample size, results represent preliminary findings that need replication. Further, in the absence of a placebo arm, we cannot confirm that the observed effects are due solely to medication. These preliminary findings suggest that SSRI treatment in adolescents impacts both cortical thickness and autonomic functioning. Confirmation of these findings would support OFC thickness and HRV as neurobiological mediators of treatment outcome.